Evaluation of agricultural waste, as a substrate for the artisanal production of the Oyster Mushroom (Pleurotus Ostreatus) - Ricardo Albuja-Narváez; Ana Ruth Álvarez-Sánchez; Juan José Reyes-Pérez (Cedamaz, 2024)
Pleurotus ostreatus is one of the most consumed edible mushrooms worldwide, in Ecuador, there is not much information on the use of agricultural residues that serve as optimal substrates, nor agroclimatic adaptations of the artisanal cultivation of this fungus. The objective of this work was to evaluate different agricultural residues, as a substrate for the artisanal production of the oyster mushroom (Pleurotus ostreatus) in the community of Carmen, Loja, Ecuador. For the development of this work, three treatments with five replicates for each treatment were evaluated, the treatments were evaluated on agricultural residues of: cane bagasse (T1), coffee husk (T2) and rice chaff (T3), the variables that were measured were: earliness, biological efficiency and production rate. The statistical design used was a completely randomized design statistically evaluated by means of an ANOVA with the statistical program R. The results indicated that for the treatment with sugar cane bagasse (T1) the earliness found was between 34 and 44 days, obtaining an average production of 25% and biological efficiency 15%. For the cultivation of the fungus in the coffee husk residues (T2), growth problems were observed; in the treatment with rice chaff (T3) it presented an earliness between 52 and 81 days with an average production rate of 3.2% and an average biological efficiency of 2%. Concluding that cane bagasse is the most recommended agricultural residue for the cultivation of the fungus Pleurotus ostreatus in the community of Carmen, Loja Ecuador.